Solar Calendar : And Other Ways of Marking Time. - Bendik-Keymer, Jeremy, 1970- (Punctum Books, 2017)
At the end of his life, Pierre Hadot was a professor at the College de France and he helped Michel Foucault conceptualize ethics. Hadot devoted his career to recovering the ancient conception of philosophy, according to which the discourses of universities are but a fragment of what philosophy is. His engagement with this theme helped Bendik-Keymer understand and develop a personal counter-culture to his academic work, a kind of original academics truer to the idea of the philosophical school Plato first developed. But while Plato's school developed a useful form of life, it had an ambivalent relation to democracy and to everyday people. Whereas Plato was in some ways one of the first egalitarians, he was also deeply classist in his categorization of intellectual potentials. He effectively thought some people were stupid by nature, having no philosophical worth. Hence the Academy existed outside the city, in practice exclusive and somewhat sequestered. To some extent, Plato's vision of philosophy -- at least as explained by Hadot -- had the practical point of philosophy right, but this point still needed to be rendered thoroughly democratic in the polyphony and multiple intelligences of people. Doing so coheres with what Foucault was after in his application of Hadot. It is also what Bendik-Keymer is after -- to extract what is good from original academics and make it democratic, as opposed to dumbing people down. Imagine the kind of philosophy book you might have wished for when you were growing up. Seeking a reader who would be patient and open-minded enough to live with her own questions and to walk around town with her thoughts, this book would not have a single thesis but would rather work through multiple problems and be an experience, born out of life-experience. It would not be summarizable. It would be larger than the reader and open onto different kinds of readings. This is the kind of philosophy book that was at home in the 19th century. Solar Calendar (a follow-up to Bendik-Keymer's The Ecological Life: Discovering Citizenship and a Sense of Humanity) contains six oddities: a family portrait, a parody-essay, a time-capsule poem, an exploded essay, a poetic record of an act, and an aphorism journal for a year. Their inspirations are Epictetus' notebooks, Tarkovski's "Mirror," and Apollinaire's roving "Zone." Also experiments in ecology -- the study of home -- the six sections originate in rifts that challenge us as growing people. They alternate between environmental problems and tensions within families, as if the fissures in love and in society wash back and forth between each other as we try to make a home in the world. Multiple times layer over each other like the sounds of a large, democratic city. The personal and the planetary intersect. The space before, and against, policy where politics arises as assertion opens up in glimpses, fragmenting the body and inertia of oppressive orders. Philosophy arises as a homely and idiosyncratic practice of multiple forms of intuition, reflection and intelligence for muddling through life. Painstaking exercises in being human are grounded in unconditional love and in truthfulness -- in the desire to become.